Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/ecs2.1691
|View full text |Cite
|
Sign up to set email alerts
|

Biological soil crust and disturbance controls on surface hydrology in a semi‐arid ecosystem

Abstract: Abstract. Biological soil crust communities (biocrusts) play an important role in surface hydrologic processes in dryland ecosystems and can be dramatically altered with soil surface disturbance. In this study, through a simulated rainfall experiment, we examined biocrust hydrologic responses to disturbance (trampling and scraping) at different developmental stages on sandy soils on the Colorado Plateau. Our results showed that all disturbance treatments of the early-successional light cyanobacterial biocrusts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 54 publications
4
49
0
Order By: Relevance
“…The most significant effect of disturbance in arid areas is the destruction of microbiotic soil crusts (Faist et al. ), which in hot deserts has been shown to impede annual plant recruitment (Prasse and Bornkamm , Belnap et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The most significant effect of disturbance in arid areas is the destruction of microbiotic soil crusts (Faist et al. ), which in hot deserts has been shown to impede annual plant recruitment (Prasse and Bornkamm , Belnap et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this effect was modulated by rainfall intensity; despite its magnitude, if the intensity of a rainfall event was high, soil water gains turned to be lower than expected. Many studies have evaluated the effects of the amount and intensity of rainfall on infiltration and run‐off (e.g., Cantón et al, ; Chamizo, Cantón, Rodríguez‐Caballero, et al, ; Faist, Herrick, Belnap, Zee, & Barger, ; Kidron & Yair, ). Our results are similar to those of Chamizo, Cantón, Rodríguez‐Caballero, et al () and Kidron and Yair (), who observed that biocrust‐dominated soils had the ability to reduce run‐off when compared to bare ground soils under low intensity rainfall events.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the intensity of the rainfall event was high, biocrusts lost their capacity to reduce run‐off. Faist et al () observed that under high intensity rainfalls, the capacity to reduce run‐off was dependent on the successional stage of the biocrusts, late successional biocrusts had the capacity to reduce run‐off, whereas early successional biocrust lost this capacity. Moreover, the higher the initial soil moisture, the lower the water gains after rainfall events.…”
Section: Discussionmentioning
confidence: 99%
“…Biocrust microbial activity produces extracellular organic exudates that alter the immediate environment by supporting a stable structure and altering the water retention and transport properties of the biocrusts (Mazor et al, 1996;Belnap and Lange, 2002;Belnap, 2003;Rodríguez-Caballero et al, 2015). The resulting modification of local hydrological processes, such as infiltration run-off and water storage (Chamizo et al, 2012), enhances the capability of other organisms to cope with water scarcity (Chamizo et al, 2016;Faist et al, 2017). Furthermore, this water-regulating function of biocrusts also protects the soil surface against wind and water erosion (Belnap and Gillette, 1998;Warren, 2001).…”
Section: Introductionmentioning
confidence: 99%